Analisis dan Implementasi Penguat Jaringan Wireless Local Area Network (WLAN) - Tri Dian Alfarisi; Fatoni (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
In line with the rapid development of technology, SDN 30 Talang Kelapa which has a WLAN network in it, but the WLAN signal cannot cover all the rooms in SDN 30 Talang Kelapa. Considering that currently all teaching and learning activities in the world of education, both elementary, junior high and high school or vocational schools have recommended the teaching and learning process using computer media and smartphones to be able to access the internet to get information from the internet. In this study, the author has the aim of increasing and expanding the coverage of the Wireless LAN connection signal at SD N 30 Talang Kelapa. The test method used is wifi Analyzer software using Field Research and Library Research methods for data collection methods and guidelines for testing WLAN networks and implementing WLAN network amplifiers referring to the Network Development Life Cycle (NDLC) development model. In this study, entitled Analysis and Implementation of a WLAN network amplifier referring to the Network Development Life Cycle (NDLC) research method, it can be concluded that strengthening a WLAN network by adding a Repeater or Wifi Range Extender is more efficient in saving time and costs in its implementation. Adding a Repeater or Wifi Range Extender to expand and strengthen the WLAN network is considered very effective. Changing the login password to the wifi network in order to maintain network security and network use from unauthorized people, the number of users/clients connected to the network is not too much because it can reduce throughout in the network and there is a need for additional Internet Bandwidth from the Provider so that the Internet Network is there can be more adequate.